2016
DOI: 10.1128/msystems.00009-16
|View full text |Cite
|
Sign up to set email alerts
|

Is the Evolution of Salmonella enterica subsp.entericaLinked to Restriction-Modification Systems?

Abstract: The evolution of bacterial pathogens, their plasticity and ability to rapidly change and adapt to new surroundings are crucial for understanding the epidemiology and public health. With the application of genomics, it became clear that horizontal gene transfer played a key role in evolution. To understand the evolution and diversification of pathogens, we need to understand the processes that drive the horizontal gene transfer. Restriction-modification systems are thought to cause rearrangements within the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 63 publications
6
91
0
Order By: Relevance
“…It was previously found that for many bacteria, including some of the studied species, the pangenome is not closed, meaning that with the sequencing of additional strains new pangenes will be added to the pangenome (Rasko et al, 2008 ; Gordienko et al, 2013 ; Holt et al, 2015 ; Rouli et al, 2015 ; Maiden and Harrison, 2016 ; Roer et al, 2016 ). Thus, despite the high number of strains analyzed in each species, it is still possible that we do not capture the whole diversity of the “rare” pangenome in these species and underestimate the amount of shared “rare” pangenes.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously found that for many bacteria, including some of the studied species, the pangenome is not closed, meaning that with the sequencing of additional strains new pangenes will be added to the pangenome (Rasko et al, 2008 ; Gordienko et al, 2013 ; Holt et al, 2015 ; Rouli et al, 2015 ; Maiden and Harrison, 2016 ; Roer et al, 2016 ). Thus, despite the high number of strains analyzed in each species, it is still possible that we do not capture the whole diversity of the “rare” pangenome in these species and underestimate the amount of shared “rare” pangenes.…”
Section: Resultsmentioning
confidence: 99%
“…The virulence analysis identified 14 Salmonella Pathogenicity Islands. The identified SPIs were typical for S. Gallinarum and few in numbers (1-14 SPI, [29]).…”
Section: Discussionmentioning
confidence: 96%
“…Antibiotic resistance (ABR) determinants in genomes were predicted using ResFinder (90% threshold for identity and 60% for minimum length) ( Zankari et al, 2012 ) to identify acquired ABR genes and PointFinder (90% threshold for identity and 60% for minimum length) ( Zankari et al, 2017 ) to identify point mutations conferring ABR. The representative subset of the isolates ( n = 31) was also examined for virulence factors using VirulenceFinder ( Joensen et al, 2014 ) and VFDB VFanalyzer ( Liu et al, 2018 ) and Salmonella Pathogenicity Islands (SPIs) using SPIFinder (v1.0; 95% threshold for identity and 60% for minimum length) ( Roer et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%